HEGEMONY AND RESISTANCE IN FICTION “IN OTHERS ROOM, OTHER WONDERS” BY DANIYAL MUEENUDDIN - Sehar Imtiaz; Mahwish Robab; Dr. Muhammad Arfan Lodhi (International Journal of Contemporary Issues in Social Sciences, 2024)
The study underwent thematic and content analysis of the short stories mentioned in the novel “In other rooms’ other wonder” written by Daniyal Mueenuddin. The novel achieved significant kudos and literary appreciation regarding art of narration, linguistic incorporation, thematic concerns, and cultural representation. The stories have been written in Pakistani rural and urban aspects, as well as in foreign cultural perspectives of native Pakistanis. To pursue this study, the researcher chosen exploratory framework. The whole book was taken as sample of the study to undergo thematic and content analysis. The content analytic framework consisted upon four categories including thematic, hegemonic, counter-hegemonic, and meta-analysis category. Thematic analysis underwent characterization, setting, plot, theme and PoV; Cultural hegemony analysis consisted upon the factors of narration, representation, language, symbolism, and power-dynamics, whereas counter-hegemonic category discussed counter discourse, resistance, subaltern, revitalization and political discourse. The findings of the study highlighted that author depicts the marginalization and emancipation of subaltern class among inter-elite and intra-elite segments of the society. Even the elites, when reside in foreign countries, face weird sense of deprivation and alienation. The stories further highlight the broken faith, shallow spiritualism, shattered ethical standards, corrupt moral practices, intoxicated indulged habits, and infatuated sensual attachments earning more kicks than kudos by common and ordinary readers. However, it is also found that author used impressive rhetoric, expressive symbolism, heart touching narration, and astounding art of characterization.